2020
DOI: 10.1186/s12917-020-02507-z
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-responsive vaginal leiomyoma and hyperprogesteronemia due to ovarian luteoma in an older bitch

Abstract: Background: This is the first report about a vaginal leiomyoma concomitant with an ovarian luteoma in a bitch. Case presentation: A 11-year-old intact female Labrador retriever was referred because of anuria, constipation and protrusion of a vaginal mass through the vulvar commissure. The bitch had high serum progesterone concentration (4.94 ng/ml). Because of the possibility of progesterone responsiveness causing further increase of the vaginal mass and since the bitch was a poor surgical candidate a 10 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…No specific breed predisposition was reported for the condition, however few reports recorded certain breeds are spitz, Labrador retriever and non-descript breed of dogs. 6,7 The clinical signs were in congruence with the reports presented earlier like hard mass protruded from vaginal canal by Balamurugan and Sivasudharsan. 6 The size, position and number of vaginal fibroma mass requiring episiotomy for complete surgical removal of the mass maybe the first choice.…”
Section: Discussionsupporting
confidence: 86%
“…No specific breed predisposition was reported for the condition, however few reports recorded certain breeds are spitz, Labrador retriever and non-descript breed of dogs. 6,7 The clinical signs were in congruence with the reports presented earlier like hard mass protruded from vaginal canal by Balamurugan and Sivasudharsan. 6 The size, position and number of vaginal fibroma mass requiring episiotomy for complete surgical removal of the mass maybe the first choice.…”
Section: Discussionsupporting
confidence: 86%
“…Hyperprogesteronemia has previously been reported in a bitch with ovarian luteoma, 9 and in women with ovarian Sertoli cell tumour, 10 granulosa cell tumour 11 and Leydig cell tumour 12 . In Case 1, we did not investigate a potential ovarian origin to the excessive production of progesterone, as no ovarian abnormalities were found on imaging.…”
Section: Discussionmentioning
confidence: 97%
“…Vaginal fold prolapse occurs due to the elevated levels of estrogens during the proestrus and estrous stages of the sexual cycle (Sontas et al, 2010;Anila et al, 2020). The development and growth of the vaginal masses are considered to be stimulated by ovarian steroids and growth factors (Zhao et al, 2003;Ferré-Dolcet et al, 2020). The stage of the estrous cycle can be interpreted by vaginal cytology.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of steroidal hormones receptor antagonists was reported as an alternative treatment option because the growth of these masses may be stimulated by ovarian steroids (Rollón et al, 2008;Sathya and Linn, 2014). Ferré-Dolcet et al (2020) reported a case of progesteronesensitive vaginal leiomyoma in which they emphasized the importance of identifying progesterone-related conditions in order to decide on effective treatment as a combined medical and surgical approach.…”
mentioning
confidence: 99%